A case of partial empty sella turcica syndrome: Sheehan syndrome - Assudani, Lata; Notwani, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Sheehan syndrome is the clinical manifestation that results due to necrosis of pituitary gland resulting from severe postpartum haemorrhage during pregnancy and is one of the causes of empty sella, complete absence of the pituitary gland. Partial empty sella is the term given when part of the gland is visible on imaging. The hormonal deficiencies and resulting clinical syndromes are thus respectively named as complete/empty sella syndrome and partial empty sella syndrome. Incidence of empty sella especially partial empty sella are extremely rare. Also, Sheehan syndrome as a cause of the same has not been frequently observed. Here, we present a case of a young female who presented with secondary amenorrhoea postpartum and was diagnosed ultimately to have partial empty sella syndrome and partial Sheehan syndrome.